Development of suicide postvention guidelines for secondary schools: a Delphi study. (December 2016) - Cox, Georgina; Bailey, Eleanor; Jorm, Anthony; Reavley, Nicola; Templer, Kate; Parker, Alex; Rickwood, Debra; Bhar, Sunil; Robinson, Jo
Abstract Background Suicide of school-aged adolescents is a significant problem, with serious implications for students and staff alike. To date, there is a lack of evidence regarding the most effective way for a secondary school to respond to the suicide of a student, termed postvention [(Crisis 33:208-214, 2012), (Crisis 34:164-182, 2013)]. The aim of this study was to employ the expert consensus (Delphi) methodology to the development of a set of guidelines, to assist English-speaking secondary schools to develop a plan to respond to a student suicide, or to respond to a suicide in the absence of a predetermined plan. Methods The Delphi methodology was employed, which involved a two-stage process. Firstly, medical and research databases, existing postvention guidelines developed for schools, and lay literature were searched in order to identify potential actions that school staff could carry out following the suicide of a student. Based on this search, an online questionnaire was produced. Secondly, 40 experts in the area of suicide postvention from English-speaking countries were recruited and asked to rate each action contained within this questionnaire, in terms of how important they felt it was to be included in the postvention guidelines. A set of guidelines was developed based on these responses. In total, panel members considered 965 actions across three consensus rounds. Results Five hundred fourty-eight actions were endorsed for inclusion into the postvention guidelines based on an 80 % consensus agreement threshold. These actions were groups according to common themes, which are presented in the following sections: 1. Developing an Emergency Response Plan; 2. Forming an Emergency Response Team; 3. Activating the Emergency Response Team; 4. Managing a suspected suicide that occurs on school grounds; 5. Liaising with the deceased student's family; 6. Informing staff of the suicide; 7. Informing students of the suicide; 8. Informing parents of the suicide; 9. Informing the wider community of the suicide; 10. Identifying and supporting high-risk students; 11. Ongoing support of students; 12. Ongoing support of staff; 13. Dealing with the media; 14. Internet and social media; 15. The deceased student's belongings; 16. Funeral and memorial; 17. Continued monitoring of students and staff; 18. Documentation; 19. Critical Incident Review and annual review of the ER Plan; 20. Future prevention. Panel members frequently commented on every suicide being 'unique', and the need for flexibility in the guidelines, in order to accommodate the resources available, and the culture of the school community. Conclusion In order to respond effectively and safely to the suicide of a student, schools need to undertake a variety of postvention actions. These are the first set of postvention guidelines produced worldwide for secondary schools that are based on expert opinion using the Delphi method.